Electrochemical Analysis of Corrosion Inhibition of Low Carbon Steel in 0. 1 N HCl by Bottle Gourd Peels - Srivastava P.; Pal S.; Jha V.K.; Ji G.; Prakash R. (My University, 2025)
Corrosion of metals greatly affects its efficacy of being functional in the surrounding environment. This can have a big impact on the economy and can cause risk to the humans. These negative effects of corrosion can be minimized in different ways; however, use of a biodegradable and cheap inhibitor is a better choice for this purpose. This work discusses use of a similar kind of biodegradable inhibitor (Bottle Gourd peels) for low carbon steel (LCS) corrosion prevention in 0.1 N HCl. Aqueous extract of Bottle Gourd peels (AEBGP) is tested by UV–visible spectroscopy (UVS), FTIR spectroscopy (FTIRS), open circuit potential (OCP) curves, electrochemical impedance spectroscopy (EIS), Tafel polarization curves (TPC), and scanning electron microscopy (SEM). The analysis of AEBGP by UVS and FTIRS reveals that AEBGP possesses several biomolecules. These biomolecules may adsorb on LCS and thus can protect LCS from corrosion. Based on investigation in this work, the maximum inhibition received is 83% (TPC). The inhibition is also realized in SEM images. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.